A high-quality genome of the early diverging tychoplanktonic diatom Paralia guyana - Eva C. Sonnenschein (Scientific Data, 2024)
The diatom Paralia guyana is a tychoplanktonic microalgal species that represents one of the early diverging diatoms. P. guyana can thrive in both planktonic and benthic habitats, making a significant contribution to the occurrence of red tide events. Although a dozen diatom genomes have been sequenced, the identity of the early diverging diatoms remains elusive. The understanding of the evolutionary clades and mechanisms of ecological adaptation in P. guyana is limited by the absence of a high-quality genome assembly. In this study, the first high-quality genome assembly for the early diverging diatom P. guyana was established using PacBio single molecular sequencing. The assembled genome has a size of 558.85 Mb, making it the largest diatom genome on record, with a contig N50 size of 26.06 Mb. A total of 27,121 protein-coding genes were predicted in the P. guyana genome, of which 22,904 predicted genes (84.45%) were functionally annotated. This data and analysis provide innovative genomic resources for tychoplanktonic microalgal species and shed light on the evolutionary origins of diatoms.